Victims' perceptions of police services: The perspectives of tourists as outsiders. (June 2022) - Mawby, Rob I; Ozascilar, Mine
This article presents the first research to consider perceptions of the police held by non-resident victims, in this case US citizens on holiday either at home or abroad. Based on a small sample of 84 US residents victimised while holidaying in either the USA or four other countries, and drawn from Mechanical Turk (MTurk), a crowdsourcing platform, it is, essentially exploratory. However, the findings suggest that tourist victims in our sample commonly reported their crimes and held extremely positive views of the way they were treated by the police, indeed more so than their experiences 'back home' had led them to expect. Most victims, nevertheless, said they would have appreciated more support, from the police and other sources. Although more research is needed to build on this study, the findings do underline the need for a greater focus on the experiences of foreign visitors and offer a template for future research on outsiders' views of their experiences as victims.